Application of the Two-Phase Simplex Method and the Two-Phase Quick Simplex Method in Minimizing Raw Material Costs People with Diabetes Mellitus - Elfira Safitri; Rizka Yuliani; Sri Basriati; Mohammad Soleh (Jurnal Sains Matematika dan Statistika, 2026)
Diabetes Mellitus (DM) is a long-term metabolic disease or disorder caused by various factors and is characterized by an increase in high blood sugar levels, accompanied by dysfunction in the metabolism of carbohydrates, fats, and proteins as a result of impaired insulin function. Ibnu Sina Hospital Pekanbaru provides treatment to patients suffering from Diabetes Mellitus by applying a type IV diet with normal nutritional status and BMI in the interval of 18 to 25 BMI. In the process of making food, Ibnu Sina Hospital uses raw materials such as rice, fish, tempeh, broccoli and bananas. The purpose of the study is to find out the minimum cost that must be incurred for food raw materials at Ibnu Sina Hospital Pekanbaru for patients with Diabetes Mellitus. The methods used are the two-phase simplex method and   the two-phase quick simplex method. Based on the results of this study, the two-phase simplex method requires 5 iterations, while   the two-phase quick simplex method only requires 1 iteration to obtain optimal results. So that the quick simplex method is more efficient than the two-phase simplex method because it is seen from the number of iterations carried out. In both methods, it was obtained that the minimum production cost of food raw materials for patients with diabetes mellitus was Rp. 9,138.5.